On adding over-identifying instrumental variables to simultaneous equations. - Hendry, D (Elsevier, 2011)

(untitled)
Reducing the number of over-identifying instruments, or adding them to a structural equation, increases estimation dispersion. Added instruments should be insignificant under correct specification, with parameter estimates nearly unaffected, confirmed by Monte Carlo. Selecting instruments does not affect these results.